Legal and constitutional disputes and the Philippine economy - Gerardo P. Sicat (University of the Philippines, School of Economics (UPSE), 2007)
The Philippines became independent in 1946 but its legal and constitutional framework was erected in the 1935 Constitution. The 1987 Constitution did little to change these provisions in the midst of economic reforms that were undertaken to improve the legal basis of doing business and promoting economic development. The study first undertakes a review of court cases and the backlogs in the justice delivery system. The heavy backlogs in the justice system which is indicative of a litigious business environment create a drag on overall economic performance. But the economic restrictions that remain in the constitution have played the role of iron economic laws because of their relative permanence in the legal framework. These restrictions contributed to the difficulties experienced in all branches of the government - executive, legislative, and judicial - to effect a cohesive economic reform process that could encourage the inflows of foreign capital to raise investment and productivity. Endowed with relatively more capital at the start of independence in 1946 and therefore a likely candidate for head start and sustained growth, the Philippines instead fell behind the high growth economies of East Asia.
Keywords: 330; Verfassung; Rechtsordnung; Makroökonomischer Einfluss; Wirtschaftswachstum; Verfassungsökonomik; Rechtsökonomik; Philippinen